Concessions of an alpha male? Cooperative defence and shared reproduction in multi-male primate groups - Snyder-Mackler, Noah (The Royal Society, 2012)
By living in social groups with potential competitors, animals forgo monopolizing access to resources. Consequently, debate continues over how selection might favour sociality among competitors. For example, several models exist to account for the evolution of shared reproduction in groups. The ‘concession model’ hypothesizes that dominant reproducers benefit from the presence of subordinates, and hence tolerate some reproduction by subordinates. This mutual benefit to both dominants and subordinates may provide a foundation for the formation of social groups in which multiple members reproduce—a necessary step in the evolution of cooperation. To date, however, the concession model has received virtually no support in vertebrates. Instead, the vast majority of vertebrate data support ‘limited control models’, which posit that dominant reproducers are simply unable to prevent subordinates from reproducing. Here we present the most comprehensive evidence to date in support of the concession model in a vertebrate. We examined natural variation in the number of adult males in gelada (Theropithecus gelada) reproductive units to assess the extent of reproductive skew in multi-male units. Dominant (‘leader’) males in units that also had subordinate (‘follower’) males had a 30 per cent longer tenure than leaders in units that did not have followers, mainly because followers actively defended the group against potential immigrants. Follower males also obtained a small amount of reproduction in the unit, which may have functioned as a concession in return for defending the unit. These results suggest that dominants and subordinates may engage in mutually beneficial reproductive transactions, thus favouring male–male tolerance and cooperation.